A diagnostic index for predicting heart rate variability decline and prognostic value in newly diagnosed non-small cell lung cancer patients - Zhang, Lifang; Liu, Ying; Han, Di; Wang, Yan; Geng, Fanqi; Ding, Wei; Zhang, Xuejuan (Frontiers in Oncology, 2024)
BackgroundHeart rate variability (HRV) is an important marker of autonomic nervous system function and cardiovascular health. Holter monitoring is a crucial method for evaluating HRV, but the procedure and result analysis are relatively complex. This study aims to develop a simplified diagnostic index for predicting HRV decline in newly diagnosed non-small cell lung cancer (NSCLC) patients and evaluate its prognostic value.MethodsThis retrospective cross-sectional study included 131 newly diagnosed NSCLC patients. Baseline characteristics were compared between normal HRV group and declined HRV group. Univariate and multivariate logistic regression analyses identified significant predictors of HRV decline. A diagnostic index was developed based on resting heart rate (RHR), serum sodium, and interleukin-6 (IL-6) and externally validated. Kaplan-Meier survival analysis assessed the prognostic value of the index.ResultsPatients with declined HRV had higher median RHR (84 b.p.m. vs. 70 b.p.m., p < 0.001), lower serum sodium (136.3 mmol/L vs. 138.7 mmol/L, p < 0.001), lower serum albumin (39 g/L vs. 41 g/L, p = 0.031), higher lactate dehydrogenase (LDH) (202 U/L vs. 182 U/L, p = 0.010), and higher IL-6 (11.42 pg/ml vs. 5.67 pg/ml, p < 0.001). Multivariate analysis identified RHR (OR = 3.143, p = 0.034), serum sodium (OR = 6.806, p < 0.001), and IL-6 (OR = 3.203, p = 0.033) as independent predictors of HRV decline. The diagnostic index, with an area under the curve (AUC) of 0.849, effectively predicted HRV decline. ROC analysis of the external validation data demonstrated an AUC of 0.788. Survival analysis showed that patients with a diagnostic index > 2 had significantly worse overall survival (log-rank p < 0.001).ConclusionsThe study identified key clinical parameters that predict HRV decline in newly diagnosed NSCLC patients. The developed diagnostic index, based on RHR, serum sodium, and IL-6, effectively stratifies patients by HRV status and has significant prognostic value, aiding in early identification and management of high-risk patients.